2001
DOI: 10.1029/2000jc000776
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the transient response of the Kuroshio leading to the large meander formation south of Japan

Abstract: Figure 1). After the small meander passes Cape Shiono-misaki, it slows down and rapidly amplifies in -1 month so that the Kuroshio loops back west of the Izu-Ogasawara Ridge. Then the sharpness of the meander trough gradually relaxes and the LM path is attained. The small meander generated off the southeastern coast of Kyushu is therefore often called the "trigger meander" [Solomon, 1978]. Although the generation of a small meander off the southeastern coast of Kyushu is observed in winter or early spring almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 21 publications
17
50
0
Order By: Relevance
“…Observational studies using satellite altimetry have suggested that the small meander southeast of Kyushu is generated as a result of interaction between the Kuroshio and a mesoscale eddy propagating westward from the Kuroshio recirculation region Hanawa, 2001, 2003;Mitsudera et al, 2001;Kamachi et al, 2004]. The mechanism of the subsequent evolution of the small meander into the large meander have been investigated by recent modeling studies [Endoh and Hibiya, 2001;Miyazawa et al, 2004;Tsujino et al, 2006]. They have suggested that baroclinic instability is essentially responsible for the large meander formation.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies using satellite altimetry have suggested that the small meander southeast of Kyushu is generated as a result of interaction between the Kuroshio and a mesoscale eddy propagating westward from the Kuroshio recirculation region Hanawa, 2001, 2003;Mitsudera et al, 2001;Kamachi et al, 2004]. The mechanism of the subsequent evolution of the small meander into the large meander have been investigated by recent modeling studies [Endoh and Hibiya, 2001;Miyazawa et al, 2004;Tsujino et al, 2006]. They have suggested that baroclinic instability is essentially responsible for the large meander formation.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Previous modeling studies [Hurlburt et al, 1996;Endoh and Hibiya, 2001;Miyazawa et al, 2004Miyazawa et al, , 2005aTsujino et al, 2006] have suggested that the Kuroshio large meander is generated through the baroclinic instability that occurs southeast of the Kii Peninsula. From this viewpoint, we examined both the horizontal and vertical distributions For example, in the wTM (wt05) case, negative SSHA (e.g., ÀSSHA(i, j)) at 29°-34°N, 130°-134°E on 8 May 2004 was changed to the same spatial pattern of positive sign with half amplitude (e.g., (0.5) SSHA(i, j)).…”
Section: Distributions Of Vertical Velocity Near the Kuroshio Path Somentioning
confidence: 99%
“…[15] Previous modeling and observational studies have suggested that the trigger meander southeast of the Kyushu Island [e.g., Solomon, 1978;Endoh and Hibiya, 2001] and mesoscale eddies [e.g., Ebuchi and Hanawa, 2003;Miyazawa et al, 2004Miyazawa et al, , 2005a [16] To identify key factors responsible for the large meander growth southeast of the Kii Peninsula in July 2004, we conducted three sensitivity experiments with the amplitude of each factor weakened in the initial conditions: weak trigger meander, weak anticyclonic eddy, and weak cyclonic eddy (hereafter wTM, wAE, and wCE, respectively). Table 1 (on 8 May 2004) indicates that the trigger meander was weakened in the wTM case, that the cyclonic eddy disappeared in the wCE case, and that the anticyclonic eddy was weakened in the wAE case.…”
Section: Perturbed Runs Of the Large Meander Formation In 2004mentioning
confidence: 99%
See 2 more Smart Citations